Combined Effects of Microplastics and Biochar on the Removal of Polycyclic Aromatic Hydrocarbons and Phthalate Esters and Its Potential Microbial Ecological Mechanism - Ren, Xinwei; Tang, Jingchun; Wang, Lan; Sun, Hongwen (Frontiers in Microbiology, 2021)
Microplastics (MPs) have been attracting wide attention. Biochar (BC) application could improve the soil quality in the contaminated soil. Currently, most studies focused on the effect of MPs or BC on the soil properties and microbial community, while they neglected the combined effects. This study investigated the combined effects of BC or ball-milled BC (BM) and polyethylene plastic fragments (PEPFs) and degradable plastic fragments (DPFs) on the removal of polycyclic aromatic hydrocarbons (PAHs) and phthalate esters (PAEs) from the PAH-contaminated soil and the potential microbial ecological mechanisms. The results showed that BC or BM combined with PEPF could accelerate the removal of PAHs and PAEs. PEPF combined with BM had the most significant effect on the removal of PAHs. Our results indicating two potential possible reasons contribute to increasing the removal of organic pollutants: (1) the high sorption rate on the PEPF and BC and (2) the increased PAH-degrader or PAE-degrader abundance for the removal of organic pollutants.